The $500 cup of coffee eaudiobook A lifestyle approach to financial independence. - Kramer, David (Your Coach Digital, 2016)
Why are you paying $500 for a cup of coffee? "Well, if you're a baby-boomer like me, you're not," says author Steve Lome, "but if you're 20-something, the future value of one week of gourmet coffee could easily exceed $500. When you invest, rather than ingest your coffee money, you can achieve financial independence one coffee cup at a time." Lome, a residential real estate developer, and co-author, David Kramer, a mortgage broker, nearly lost their shirts when the housing market crashed in 2008. Picking up the pieces, they wrote The $500 Cup of Coffee® to inform and inspire others to build and hold onto to their wealth. Writing in a friendly style, they demonstrate that managing money is not difficult, investment is not scary, and that financial security is within reach, especially if you're young enough and mindful enough to invest your time wisely. If you don't understand money and how it works, they explain financial jargon in simple English and illustrate complex concepts like compound interest and opportunity cost with easy-to-follow real life examples. If you have a problem relationship with money, they'll calm your anxieties by helping you take control of your money and setting realistic financial goals. If you're comfortable managing your money, they'll guide you to financial independence one sure step at a time. Rather than tell you what to do, they make your think. While encouraging responsible spending and consistent savings, they take a big picture view of everything from education to retirement including home, work, family, and happiness. When you see how the pieces fit together, you'll ask better questions and make better choices. Not only will you build your wealth, you'll use it to make life better.